Curcumin exerts protective effects against doxorubicin-induced cardiotoxicity - O. О. Klymenko; T. I. Drevytska; O. O. Gonchar; K. V. Tarasova; V. I. Nosar; V. Ye. Dosenko; I. M. Mankovska (The Ukrainian Biochemical Journal, 2025)
The mechanism of doxorubicin (Dox) cardiotoxicity involves different pathways, including oxidative stress and mitochondrial dysfunction. It’s supposed that pharmacological effect on HIF gene expression may protect the heart against the detrimental effects of the doxorubicin-induced injury. We hypothesized that the cardioprotective effects of Curcumin (Curc) are exerted by regulating HIF and its target genes expression. To test this, an in vitro model of Dox-induced injury to primary myocardial cardiomyocytes was used. Isolated Wistar rat neonatal cardiomyocytes were incubated in the culture medium for 24 h in control, either with Dox (0.5 μmol/ml) or Curc (20 μmol/ml), or in their combination in the same doses. Mitochondria were isolated from rat cardiomyocytes culture. It was demonstrated that cardiomyocytes exposure to Dox led to an increase in the activity of oxidative stress markers in isolated mitochondria, a decrease in the efficiency of the respiratory chain and phosphorylation processes, decline of membrane potential and the rate of K+ ions entry into mitochondria. Doxorubicin inhibited the expression of mRNA of both HIF-1α, 2α, 3α subunits and its important target genes PDK-1 and IGF-1 in mitochondria. A negative impact on the cardiomyocyte contractile activity was observed. The combined use of doxorubicin with curcumin led to an increase of cardiomyocytes viability and attenuation of oxidative stress in mitochondria, prevented the development of mitochondrial dysfunction and significantly improved the contractile activity of cardiomyocytes.